Towards a clinical application of freeze-dried squalene-based nanomedicines. (3rd July 2019) - Rouquette, Marie; Ser-Le Roux, Karine; Polrot, Mélanie; Bourgaux, Claudie; Michel, Jean-Philippe; Testard, Fabienne; Gobeaux, Frédéric; Lepetre-Mouelhi, Sinda
Abstract: Squalene-adenosine (SQAd) nanoparticles (NPs) were found to display promising pharmacological activity similar to many other nanomedicines, but their long-term stability was still limited, and their preparation required specific know-how and material. These drawbacks represented important restrictions for their potential use in the clinic. Freeze-drying nanoparticles is commonly presented as a solution to allow colloidal stability, but this process needs to be adapted to each nanoformulation. Hence, we aimed at developing a specific protocol for freeze-drying SQAd NPs while preserving their structural features. NPs were lyophilised, resuspended and analysed by dynamic light scattering, atomic force microscopy and small-angle scattering. Among four different cryoprotectants, trehalose was found to be the most efficient in preserving NPs physico-chemical characteristics. Interestingly, we identified residual ethanol in NP suspensions as a key parameter which could severely affect the freeze-drying outcome, leading to NPs aggregation. Long-term stability was also assessed. No significant change in size distribution or zeta potential could be detected after three-month storage at 4 °C. Finally, freeze-dried NPs innocuity was checked in vitro on cultured hepatocytes and in vivo on mice. In conclusion, optimisation of freeze-drying conditions resulted in safe lyophilised SQAd NPs that can be easily stored, shipped and simply reconstituted into an injectable form.